DEVELOPMENT OF MASS SPORTS IN INSTITUTIONS AND ORGANIZATIONS (International journal of artificial intelligence, 2025)
This article covers the need, importance and practical ways to develop mass sports in organizations. Particular attention is paid to the role of mass sports in the formation of a healthy lifestyle in labor communities, increasing the physical activity of employees and ensuring productivity of work. The analysis shows that in organizations that have introduced sporting events, the socio-psychological environment improves, loyalty to work increases, and wellness indicators become higher. The article provides suggestions and recommendations for the formation of a sports culture in organizations, the introduction of intramural sports programs, the development of sports infrastructure and the promotion of employees.